PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA EKSPOR PERUSAHAAN PADA PT SARIKAYA SEGA UTAMA BANJARBARU KALIMANTAN SELATAN - Halimah Tussaddiah; Muhammad Helmi; Maghdalena Yoeseran (Universitas Lambung Mangkurat, 2020)
Industrial companies certainly have a fundamental goal to increase performance. Concepts that can be used to achieve corporate performance goals are market orientation and product innovation. Market orientation is the behavior of the organization in order to provide the best value to customers by finding customer desires and needs, product innovation is the behavior of the organization as product progress that can bring products one step ahead of competing products. Determination of the object of this research is at PT Sarikaya Sega Banjarbaru South Kalimantan to prove whether market orientation has a significant effect on company performance and whether innovation has a significant effect on company performance. The purpose of this study was to analyze the effect of market orientation on the performance of PT Sarikaya Sega Utama and analyze the effect of product innovation on the company's performance at PT Sarikaya Sega Utama. The unit of analysis in this study was all of PT Sarikaya Sega Utama's export products. Respondents in this study were company directors, company managers, marketing managers, production managers and financial managers. Hypothesis testing proved that there was no significant effect between market orientation on company performance where the value of t value was 0.822 and p value was 0.412, while the second hypothesis proved that there was no significant effect between product innovation on company performance where the value of t value was 1.009 and p value was 0.314.Keywords: Marketing orientation; Product innovation; Firm Performance